FDNC5 Genetic Polymorphism in Patients with Peripartum Cardiomyopathy - Ali Altaher; Mohamed eid; Hesham moslem; Amal Ali; Samar Mustafa; Amera morad (Babol University of Medical Sciences, 2024)
Background: Late in pregnancy or soon after delivery, peripartum cardiomyopathy (PPCM) which is an uncommon type of cardiomyopathy, can develop. To assess the association between the level of irisin expression and (FNDC5) (rs3480) gene polymorphism with peripartum cardiomyopathy. Methods: This is a case control study included a thirty female patients with new-onset PPCM and sixty healthy females at the at the peripartum period in same time window for PPCM as a control.  For each patient, comprehensive medical history was taken, full clinical assessment was done, ECHO., FNDC5 (rs3480) & Irisin assay. Results: The left ventricle end diastolic dimensions &left atrium diameters were statistically significant higher in patients' group than controls' group (P=0.000 for all), Also left ventricular ejection fraction (%) was statistically significant lower in patients than controls and as regards irisin, its Mean ±SD was lower in patient group than control group (8.44±1.1 vs 10.65±2.31) with (p <0.001) which is considered a significant difference statistically. Conclusion: Irisin level was lower in peripartum cardiomyopathic patients when compared with normal individuals and regarding its genotype, the homotype A/A was higher than homotype G/G.